Rethinking Radicalization: Reinforcement Sensitivity Theory as a Framework to Understand Pathways to Political Activism and Radicalization - Shortland, Neil D. (Terrorism and political violence, 2025)
This paper proposes a theory of radicalization to violence centered on the psychological, neuropsychological, and physiological processes of human motivation. Specifically, we argue that the movement towards extremist violence is centered on motivation processes that create goal pursuit and acquisition. Here we use Reinforcement Sensitivity Theory (RST) to identify how variations in intentions to engage in extremism (measured via activism and radicalism) are a result of trait differences in the approach and withdrawal motivational pathways. We present findings from a large-n study that measures the association between RST personality variables and activism and radicalism. Overall, we found support for RST in that both behavioral inhibition system (BIS) and behavioral activation system (BAS) variables correlated with higher activism and radicalism intention scores. Furthermore, we demonstrate that certain types of motivation are more associated with intentions for activism (behavior) versus radicalism (extremist thought). Based on these findings we highlight the potential theoretical and methodological benefits of applying RST to the study of individuals’ movement towards extremist violence. Specifically, we empathize the importance of centering discussions of involvement, engagement and disengagement around the psychological process of motivation to engage (or remain engaged).